How should large and small countries be represented in a currency union? - Helge Berger; Till Mueller (Center for Economic Studies and ifo Institute (CESifo), 2004)
The likely extension of the euro area has triggered a debate on the organization of the ECB, in particular on the apparent mismatch between relative economic size and voting rights in the Council. We present a simple model of optimal representation in a federal central bank addressing this question. Optimal voting weights reflect two opposing forces: the wish to insulate common monetary policy from changing preferences at the national level, and the attempt to avoid an overly active or passive reaction to idiosyncratic national economic shocks. A perfect match between economic size and voting rights is rarely optimal, and neither is the ?one country, one vote principle?. Empirically, there are indications that the pattern of over- and under-representation of member countries in the ECB Council might be extreme by the standards of the US Fed and German Bundesbank and not always optimal.
Keywords: E52; D72; F33; E58; 330; Central Bank; Federal Central Bank; Currency Union; optimal representation; voting; ECB; Zentralbank; Europäische Wirtschafts- und Währungsunion; Abstimmungsregel; Landesgrösse; Geldpolitik; Theorie; EU-Staaten